Financial capitalism trapped in an 'impossible' profit rate. The infeasibility of a 'usual' profit rate, considering fictitious capital, and its redistributive, ecological, and political implications. (1st January 2013) - Elsner, Wolfram
This paper explores the crisis and some implications against the Marxian profit rate (PR). The PR helps explaining a number of phenomena often considered disparate. The focus is on integrating exploded fictitious capital in the PR and to estimate a corrected PR. We estimate global fictitious capital and calculate a conventional and a corrected PR for Germany. The corrected PR has reached a historical low under neo-liberalism, in spite of an increase in profit masses and profit shares in GDP, between a half and a fifth of the conventional PR (for post-WWII USA and UK, and post-1991 Germany, respectively). In contrast to the conventional PR, it also has further decreased. The financial crisis thus appears to be a crisis of dramatic over-accumulation. The consequences include reinforced redistribution and a run for transformation into real values (resources-/land-grabbing). The redistribution requirements for a 'usual' PR appear inconsistent even with formal democracy.